OP0274 CLINICAL ASPECTS, LABORATORY CHARACTERISTICS AND TREATMENT RESPONSES OF AA AMYLOIDOSIS: SINGLE CENTER EXPERIENCE WITH 163 PATIENTS. (2nd June 2020) - Bektas, M.; Koca, N.; Oguz, E.; Ince, B.; Yalçinkaya, Y.; Artim-Esen, B.; Inanc, M.; Ocal, M. L.; Gül, A.
Abstract : Background: AA amyloidosis has been associated with uncontrolled chronic inflammatory diseases such as rheumatoid arthritis (RA), ankylosing spondylitis (AS), inflammatory bowel disease (IBD) and hereditary periodic fever syndromes, and the most common cause is familial Mediterranean fever (FMF) in Turkey. Objectives: We herein aimed to evaluate clinical and laboratory characteristics and treatment responses of patients with AA amyloidosis retrospectively in a tertiary referral center. Methods: Study group was consisting of patients with biopsy proven AA amyloidosis, and their data were recorded from their charts. Treatment responses were categorized as follows: complete response was defined as no increase in serum creatinine and a proteinuria below 1gr/day; partial response as 50% decrease in proteinuria; and stable diseas e as no significant change in serum creatinine and proteinuria. Progressive disease was defined as increase in serum creatinine and/or proteinuria under treatment. Results: 173 patients were identified, and 10 patients with no biopsy result and/or missing data were excluded. A total of 163 patients (79 females, 84 males) were included in the study. Median age of patients was 45.4, and median age at diagnosis of amyloidosis was 33.5. Most common cause of amyloidosis was FMF (78.5%), followed by idiopathic cases (7.9%) and patients with AS (4.9%). A quarter (26%) of amyloidosis patients had a family history for AA amyloidosis, and 59% of patients with FMF had a family history of FMF. Amyloidosis was confirmed by renal biopsy in 76.1%, by gastrointestinal (GIS) biopsy in 11.7%, and by other biopsies in the remaining. Renal involvement was documented in 160 (98.2%) patients, while GIS involvement in 20.9%, heart in 13.5%, thyroid in 3.7% and bone marrow in 3.1%. In FMF patients, most common MEFV mutation was M694V (77.7%); and 66.7% of the patients had homozygous, 14.6% had compound heterozygous, and 18.7% heterozygous exon 10 variants. Mean age at diagnosis of amyloidosis was earlier in homozygotes (29.1) and compound heterozygotes (32.3) compared to heterozygotes (43.9) (p = 0.001). There was no difference in treatment responses, organ involvement, progression to end stage renal disease (ESRD) and mortality between monoallelic and biallelic exon 10 mutations (p = 0.42). While 44.3% (n = 70) of patients had chronic renal disease (CRD) at time of diagnosis, ESRD developed in 45.3% (n = 73) of patients. During follow-up, 55 patients underwent renal transplantation and recurrence of renal amyloidosis occurred in 24% of them. Mean creatinine and proteinuria levels at time of diagnosis were higher in patients with ESRD than those without ESRD (p <0.001, p = 0.03 respectively). Progression to ESRD was significantly higher in patients with GFR≤60 ml/min at time of admission (%14.5 vs %41.7, p=0.005, Figure 1 ). A total of 113 (70.2%) patients used biological agents, most commonly used biological agent was anakinra (n = 81). Canakinumab was used in 17 and other biological agents in 17 patients. Complete response was observed in 49.1%, partial response was observed in 6.2%, and progressive progression was observed in 21.7%. GIS and cardiac involvements were associated with progressive course (p <0.001) and increased mortality (p = 0.002, p <0.001, respectively), and overall mortality rate was 8.7%. Conclusion: Increased rate of ESRD and progression of amyloidosis findings in patients who presented with GFR<60 ml/min emphasize the importance of early diagnosis. Although mortality rate is very high in patients with AA amyloidosis due to FMF disease, it may be possible to reduce mortality with an effective treatment. Disclosure of Interests: None declared